Fiscal decentralization and the shadow economy - Petr Janský; Miroslav Palanský (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
In this paper we use the new Government Revenue Dataset to analyse fiscal decentralization. We find that developed countries are on average more decentralized than developing countries and that Asia, Europe and North America are among the most fiscally decentralized regions. In our econometric analysis, we examine the relationship between fiscal decentralization and the shadow economy. We hypothesize that decentralization can negatively or positively affect the size of the shadow economy, increasing or decreasing its size, and that this effect can vary according to a country's level of development. We first replicate earlier results of cross-country analysis and proceed by estimating a fixed effects model, which provides evidence of a relatively robust and statistically significant relationship between tax revenue decentralization and the size of the shadow economy. We find that in developing countries a higher level of decentralization is associated with an increase in the size of the shadow economy, while in developed countries the opposite effect prevails.
Keywords: H20; H71; H72; O17; 330; taxation; decentralization; fiscal decentralization; shadow economy; developing countries